2017
DOI: 10.1016/j.celrep.2017.10.109
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-Based Compound Screening and In Vitro Trials Identify a Synergistic Anti-amyloid β Combination for Alzheimer’s Disease

Abstract: In the process of drug development, in vitro studies do not always adequately predict human-specific drug responsiveness in clinical trials. Here, we applied the advantage of human iPSC-derived neurons, which offer human-specific drug responsiveness, to screen and evaluate therapeutic candidates for Alzheimer's disease (AD). Using AD patient neurons with nearly 100% purity from iPSCs, we established a robust and reproducible assay for amyloid β peptide (Aβ), a pathogenic molecule in AD, and screened a pharmace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
169
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(171 citation statements)
references
References 39 publications
2
169
0
Order By: Relevance
“…M.3243A>G heteroplasmy levels of iPS lines were sequenced, after which one iPS clone without-, and one iPS clone with heteroplasmy were selected. An additional, curated control cell line (409B2 (Kondo et al, 2017)) was included, and confirmed to have no m.3243A>G heteroplasmy. IPS cells were thawed and cultured at all times cultured on recombinant human laminin LN521 (Biolamina, 2021-21) kept in E8 basal medium (Thermo Fisher Scientific) supplemented with primocin (0.1 µg/ml, Invivogen), puromycin (0.5 µg/ml) and G418 (0.5 µg/ml), and uridine (50 µg/ml) and incubated at 37°C/5%CO2, with medium changes every 2-3 days and passages 1-2 times per week using ReLeSR (Stem Cell Technologies).…”
Section: Ips Cell Generation and Culturementioning
confidence: 99%
“…M.3243A>G heteroplasmy levels of iPS lines were sequenced, after which one iPS clone without-, and one iPS clone with heteroplasmy were selected. An additional, curated control cell line (409B2 (Kondo et al, 2017)) was included, and confirmed to have no m.3243A>G heteroplasmy. IPS cells were thawed and cultured at all times cultured on recombinant human laminin LN521 (Biolamina, 2021-21) kept in E8 basal medium (Thermo Fisher Scientific) supplemented with primocin (0.1 µg/ml, Invivogen), puromycin (0.5 µg/ml) and G418 (0.5 µg/ml), and uridine (50 µg/ml) and incubated at 37°C/5%CO2, with medium changes every 2-3 days and passages 1-2 times per week using ReLeSR (Stem Cell Technologies).…”
Section: Ips Cell Generation and Culturementioning
confidence: 99%
“…Recent studies also imply a large gap in the effectiveness of drug discovery studies between iPS-derived neurons and cultured cell lines [42]. Recently, Inoue and colleagues developed a reliable and robust iPS-based screening system for anti-Aβ drugs [43]. After incubating the differentiated neurons from iPS with PKC ligands for 24 h, Aβ42 and Aβ40 levels in the conditioned medium were calculated using electrochemiluminescence assays.…”
Section: Effects Of 1 On Aβ42/aβ40 Aβ Oligomerization and Neurotoximentioning
confidence: 99%
“…Human iPS cells of Alzheimer's patients were generated as described from skin fibroblasts [43,57] and maintained using StemFit AK02N medium (Ajinomoto, Tokyo, Japan) [64] and expanded for neural differentiation. To establish a robust and rapid differentiation method, we utilized direct conversion technology.…”
Section: Generation and Characterization Of Human Ips-derived Neuronsmentioning
confidence: 99%
“…Building on the strengths and relative maturity of adherent stem cell protocols, several PTS have provided proof-of-concept for iPSC-driven screening approaches (Kondo et al, 2017;Sterneckert et al, 2014) (also summarized in Table 1). At the same time, these approaches highlight the importance of careful hit validation strategies.…”
Section: Advances Of Stem Cell-based Pts In 2d Culturesmentioning
confidence: 99%